Real-life prosocial behavior decreases after being socially excluded by avatars, not agents. (May 2017) - Kothgassner, Oswald D.; Griesinger, Mirjam; Kettner, Kathrin; Wayan, Katja; Völkl-Kernstock, Sabine; Hlavacs, Helmut; Beutl, Leon; Felnhofer, Anna
Abstract: The concept of social exclusion has recently gained more attention in the context of online social interactions. However, there is only little data regarding the impact of virtual social exclusion on subsequent real-life social behaviors. Thus, this study set out to examine a virtual version of the common social exclusion scenario, the Cyberball-Paradigm (Williams & Jarvis, 2006), and test for behavioral consequences in a sample of 45 students. Both the virtual characters' agency and the experience of social presence were controlled for. Findings indicate that ostracized individuals show less prosocial behavior in a helping task and keep more seating distance to a confederate than included participants. Also, virtual social exclusion constitutes a significant threat to fundamental human needs like social control, self-esteem and belonging and causes an increase in uncertainty, sadness and anger as well as a decrease in happiness. Avatars and agents seemed to equally endanger human needs and lead to the same seating distance. However, avatar excluded persons also had higher levels of sadness and were less helpful than avatar included persons, who in turn were more confident. Thus, while the Media Equation Concept (Nass & Moon, 2000) holds true for the immediate reaction to social exclusion (i.e., avatars and agents equally threaten fundamental needs), the delayed emotional and behavioral reactions differ for avatars and agents, possibly because they are preceded by cognitive evaluation (c.f., Temporal Need-Threat Model ; Williams, 2009). Implications of these findings for everyday online social interactions (i.e., in MMORPGs) are discussed. Highlights: Virtual social exclusion leads to increased anger, sadness and uncertainty. Virtual social exclusion constitutes a significant threat to basic human needs. Participants excluded by avatars showed less real-life prosocial behavior. Excluded participants kept a larger seating distance to a confederate. There was no difference in social presence between avatars and agents.